2017
DOI: 10.5812/zjrms.8631
|View full text |Cite
|
Sign up to set email alerts
|

Comparing larvicidal Effect of Methanol Extract of the Aerial Parts of Henbane (Hyoscyamus niger L.) and Oleander ( Nerium oleander L.) plants on Anopheles spp Larvae (Diptera: Culicidae) in Vitro

Abstract: Background: Malaria is an infectious disease by fever and chills, anemia and splenomegaly genus Plasmodium parasite is the agent it. One of the easiest and least expensive methods to prevent this disease is removing the vector that usually by been done insecticides and chemical pesticides, but nowadays due to the damaging effects of by toxic chemicals is currently trying to organic toxic and plant compounds used to combat the pests. So in this study used from the Hyoscyamus niger L. and Nerium oleander L. to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Banadiqul Bazoor [86] Habbe Jadwar [86] Habb-e-Tinkar [86] Tiryaq-e-Nazla [86] Qurs Mukhaddir [86] Qurs Musallas [86] Safoof Moya [86] Barshasha [86] Habb-e-Jazla [86] Habb-e-Rasha [86] Habb-e-Shingraf [86] Habb-e-Sultani [87] Qurs Khashkhas [87] Habb-e-Aswad [87] Majoon Kakanaj [87] Jawarish Shahinshahi Ambri [87] Habb-e-Jiryan [88] Habb-e-Muqawwi [88] Lauq bazr-ul banj [88] Roughan Bazr-ul-Banj [89] CONCLUSION The present review emphasizes the action and uses mentioned in Unani classical literature, ethnopharmacological, photochemistry, pharmacological reports, and toxicological information of Bazr-ul-Banj (H. niger Linn.). It may be concluded that many pharmacological reports proved the claims of Unani scholar's, for example, Musakkin-e-Alam [29,31,32] (Analgesic) [51][52][53][54][55][56][57], Iltihab/warm [28,31,32,34,37,39] (inflammation) [51]; Ikhtelaj-e-Qalb [28,31,32] (cardioprotective) [80,81]; Zeequn Nafas [28,…”
Section: Azhar and Mustehasanmentioning
confidence: 98%
See 1 more Smart Citation
“…Banadiqul Bazoor [86] Habbe Jadwar [86] Habb-e-Tinkar [86] Tiryaq-e-Nazla [86] Qurs Mukhaddir [86] Qurs Musallas [86] Safoof Moya [86] Barshasha [86] Habb-e-Jazla [86] Habb-e-Rasha [86] Habb-e-Shingraf [86] Habb-e-Sultani [87] Qurs Khashkhas [87] Habb-e-Aswad [87] Majoon Kakanaj [87] Jawarish Shahinshahi Ambri [87] Habb-e-Jiryan [88] Habb-e-Muqawwi [88] Lauq bazr-ul banj [88] Roughan Bazr-ul-Banj [89] CONCLUSION The present review emphasizes the action and uses mentioned in Unani classical literature, ethnopharmacological, photochemistry, pharmacological reports, and toxicological information of Bazr-ul-Banj (H. niger Linn.). It may be concluded that many pharmacological reports proved the claims of Unani scholar's, for example, Musakkin-e-Alam [29,31,32] (Analgesic) [51][52][53][54][55][56][57], Iltihab/warm [28,31,32,34,37,39] (inflammation) [51]; Ikhtelaj-e-Qalb [28,31,32] (cardioprotective) [80,81]; Zeequn Nafas [28,…”
Section: Azhar and Mustehasanmentioning
confidence: 98%
“…Methanol extract of aerial parts and flower of H. niger had destroyed the mosquitoes Anopheles spp. larvae [81].…”
Section: Insecticidal Effectmentioning
confidence: 99%
“…Methanol extract of Hyoscyamus niger aerial parts had positive effects on destroying the Anopheles spp larvae and the most effective extract for destroying the mosquitoes Anopheles spp larvae, was the flower extract of henbane (LC50 = 0/26 ppm) (339)(340) .…”
Section: Hyoscyamus Nigermentioning
confidence: 99%
“…The maximum mortality (83%) was observed at the highest concentration (100ppm) (Mohammed, 2018). Some researchers have determined the larvicidal activity of N. oleander extracts of various plant parts against other insects (Behravan et al, 2017;Raveen et al, 2017 andSemiz, 2017).…”
Section: Characterization Of Biosynthesized Chitosan Nanoparticlesmentioning
confidence: 99%